PSIKOTERAPI ISLAM PADA PASIEN GANGGUAN JIWA AKIBAT PENYALAHGUNAAN NARKOBA DI PONDOK INABAH BANJARMASIN - Rachmaningtyas, Fratiwi; Mubarak, Mubarak (Faculty of Ushuluddin and Humanities, 2014)
South Kalimantan province is currently rated sixth in the case of drug abuse. On the other hand, the province of South Kalimantan is a province with Islamic society culture. It should be able to become a filter to form a healthy society, since Islam has a complete concept of physically and psychologically health. From the reality, the writer looked that Islamic psychotherapy could be an option as psychotherapy for patients with mental disorder caused by drug abuse and contemporary psychotherapy in addition to obtain the optimal health. Because the Islamic psychotherapy concept is proven to help deal with the psychological problems. Then, ?Pondok Inabah? is one of the places which uses Islamic psychotherapy chosen as the study site. This study aims to describe patients who suffer from mental disorders due to drug abuse and to find the Islamic psychotherapy techniques applied to patients with mental disorders as a result of drug abuse in ?Pondok Inabah?. The research finding can be used as the scientific literature for scholars working in the field of psychology; general and Islam. The materials study can be used by the practitioners who work in the field of psychotherapy, both psychologists and muslim therapists and as well as information material for the general public who is interested or has intention on the topic of Islamic psychotherapy for patients with mental disorders due to drugs.